Laboratory work in hydraulic engineering - Asawa, G. L. (New Age International (P) Ltd., Publishers, 2006)
In almost all technical institutions of learning, the laboratory work in any subject runs concurrently with the course in theory of the subject. Consequently, the students perform the laboratory work mechanically without intellectual involvement in the work. It is, therefore, necessary that the students, before conducting the experimental work, are familiarized with elementary theoretical and other aspects relevant to the experimental work. This book is an attempt to serve this objective for the subject of hydraulic engineering. The contents of the book include description of basic facilities in hydraulic engineering laboratory, elementary terms of fluid mechanics, fundamental equations governing the fluid motion, introduction to open channel flow, a note on writing laboratory reports, and instructional description of several experiments including those on basic hydraulic engineering (or fluid mechanics), pipe flow, open channel flow, boundary layers, and hydraulic structures.